2021
DOI: 10.1016/j.omtn.2021.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA: A potential diagnostic, prognostic, and therapeutic biomarker for human triple-negative breast cancer

Abstract: Triple-negative breast cancer (TNBC), which is the most malignant subtype of breast cancer (BC), accounts for 10%-20% of all BC cases. TNBC, which occurs more frequently in young women, is characterized by high rates of cell proliferation and metastasis and poor prognosis. Chemotherapy is the primary systemic therapeutic strategy for TNBC. However, chemotherapy is largely unsuccessful, and effective targeted therapies for TNBC have not been established. Therefore, it is a matter of great urgency to identify pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 141 publications
1
34
0
Order By: Relevance
“…Nowadays, there are more and more researches on the mechanism of circRNAs generation. In addition to RBP can bind to circRNAs to reduce the regulation of RBP on target genes and affect tumorigenesis (Huang C.-K. et al, 2020;Li et al, 2020;Song et al, 2021), some RBP can also regulate the generation of circRNAs, which also has an important role in tumor development (2016;Liu Z. et al, 2021;Wang et al, 2021d;Wang and Lei, 2021;Yang T. et al, 2021). The translation function of circRNAs is also becoming a hot topic, and the translation initiation mechanism of circRNAs mainly includes cap-dependent, IRES-dependent, m6adependent and small ORF-dependent translation initiation (He L. et al, 2021;Wang X. et al, 2021), and circRNAs encode proteins with the function of suppressing tumor activity and protecting proteins from degradation (Chen C.-K. et al, 2021;Wang et al, 2021d;Ma et al, 2021;Qi et al, 2021).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, there are more and more researches on the mechanism of circRNAs generation. In addition to RBP can bind to circRNAs to reduce the regulation of RBP on target genes and affect tumorigenesis (Huang C.-K. et al, 2020;Li et al, 2020;Song et al, 2021), some RBP can also regulate the generation of circRNAs, which also has an important role in tumor development (2016;Liu Z. et al, 2021;Wang et al, 2021d;Wang and Lei, 2021;Yang T. et al, 2021). The translation function of circRNAs is also becoming a hot topic, and the translation initiation mechanism of circRNAs mainly includes cap-dependent, IRES-dependent, m6adependent and small ORF-dependent translation initiation (He L. et al, 2021;Wang X. et al, 2021), and circRNAs encode proteins with the function of suppressing tumor activity and protecting proteins from degradation (Chen C.-K. et al, 2021;Wang et al, 2021d;Ma et al, 2021;Qi et al, 2021).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…In addition, exosomes play a role in coagulation, antigen presentation, immune regulation, and viral replication. Exosome contents, such as proteins, mRNAs, and miRNAs, have been shown to act in receptor cells, thereby activating multiple signaling pathways ( Kalluri and LeBleu, 2020 ; Wen et al, 2020 ; Rong et al, 2021b ; Wang et al, 2021e ; Reese and Dhayat, 2021 ; Tian et al, 2021 ). Tumor cells can secrete more exosomes than normal cells with some variation in contents, and tumor cell-derived exosomes can provide a suitable microenvironment for tumor development, such as cell proliferation, angiogenesis and metastasis, drug resistance and formation of pre-metastatic microenvironment ( Li and Wang, 2017 ; Yan and Chen, 2020 ).…”
Section: Biological Functions Of Circular Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the development of sequencing technology, researchers have found that circRNAs are widely distributed in eukaryotic cells and can be stably expressed, playing an important role in the regulation of gene expression in human cells ( Qu et al, 2017 ; Han et al, 2021 ). An increasing number of studies have shown that circRNAs have important physiopathological functions and are involved in the regulation of cell proliferation, differentiation, and apoptosis, as well as in the development of various diseases including tumors ( Altesha et al, 2019 ; Li Y. et al, 2020 ; Wu et al, 2020 ; Xu et al, 2020 ; Choudhary et al, 2021 ; Tian et al, 2021 ; Zhang et al, 2021 ). For example, circPRKAR1B regulates FZD4 expression by binding miR-361-3p, promoting the proliferation and migration of osteosarcoma cells as well as tumor susceptibility to chemotherapy resistance ( Feng Z.-h. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…With regards to the role of circRNAs in oncology, microarray analyses have indicated that partial circRNAs are aberrantly expressed in different types of cancer, such as lung adenocarcinoma, squamous cell carcinoma and glioma, and involved in their initiation and progression ( 16 18 ). Notably, circRNAs exhibit a more stable structure compared with other types of non-coding RNAs in human tissues and cells ( 19 ); therefore, several studies have been performed to investigate the expression profiles and the potential functions of circRNAs in patients with cancer ( 20 , 21 ). Previously, two studies analyzed the circRNA expression profiles in patients with PDAC; however, the differentially expressed circRNAs (DEcircRNAs) identified in these studies lacked validation in large scale clinical studies, and their associations with clinical characteristics or survival have not yet been investigated ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%